RETRACTED: Combined effect of Zinc lysine and biochar on growth and physiology of wheat (Triticum aestivum L.) to alleviate salinity stress - Zain ul Aibdin; Muhammad Nafees; Muhammad Rizwan; Shoaib Ahmad; Shafaqat Ali; Shafaqat Ali; Wael A. Obaid; Moodi Saham Alsubeie; Doaa Bahaa Eldin Darwish; Doaa Bahaa Eldin Darwish; Amany H. A. Abeed (Frontiers in Plant Science, 2023)
Globally, Food security main threaten by abiotic stress like salinity and levels amongst the majority serious environmental stressors which reduce crop yield mass production. Biochar application has received much attention in agricultural practices as it enhances crop quality and production. The present study was carried out to analyze the role of lysine zinc and biochar on growth enhancement of wheat (Triticum aestivum L. cv. PU-2011) under saline stress (EC 7.17 dSm-1). Seeds were sown in pots containing saline soil with and without 2% biochar, and foliar application of Zn-lysine (0, 1.0, and 2.0 mM) was made at different time intervals during plant growth. A combined application of biochar and Zn-lysine 2.0 mM highly improved the physiological attributes such as chlorophyll a (37%), chlorophyll b (60%), total chlorophyll (37%), carotenoids (16%), photosynthesis rate (Pn) 45%, stomatal conductance (gs) 53%, transpiration rate (Tr) 56%, and water use efficiency (WUE) 55%. The levels of malondialdehyde (MDA) 38%, hydrogen peroxide (H2O2) 62%, and electrolyte leakage (EL) 48% were decreased with the combined application of biochar and Zn-lysine 2.0 mM as compared with other treatments. The activities of catalase (CAT) 67%, superoxide dismutase (SOD) 70%, and ascorbate peroxidase (APX) 61% as well as catalase (CAT) 67% were regulated with the combined biochar and Zn-lysine 2.0 mM treatment. Similarly, the combined application of biochar and zinc-lysine (2.0 mM) enhanced the growth and yield attributes such as shoot length (79%), root fresh weight (62%), shoot fresh weight (36%), root dry weight (86%), shoot dry weight (39%), grain weight (57%), and spike length (43%) as compared with untreated control. The concentrations of sodium (Na) decreased whereas potassium (K), iron (Fe), and zinc (Zn) concentrations were enhanced in plants with the combined application of Zn-lysine and biochar. Overall, results showed that the combined application of Zn-lysine (2.0 mM) and biochar significantly inhibited the negative effect of salinity and improved the growth and physiological performance of wheat plants. The combined use of Zn-lysine and biochar might be a practical solution to tackle salt stress in plants, but field studies by growing various crops under varied environmental conditions are needed before any recommendation to farmers.